2021
DOI: 10.1186/s13030-021-00208-z
|View full text |Cite|
|
Sign up to set email alerts
|

The reliability and validity of the Japanese version of the Daily Record of Severity of Problems (J-DRSP) and Development of a Short-Form version (J-DRSP (SF)) to assess symptoms of premenstrual syndrome among Japanese women

Abstract: Purpose To assess the validity and reliability of the Japanese version of the Daily Record of Severity of Problems (J-DRSP, 24 items) for evaluating symptoms of premenstrual syndrome (PMS), and to develop a short form version of the J-DRSP. Methods Using the “DRSP-JAPAN” smartphone app, we collected daily J-DRSP records from cycle day − 6 (CD − 6) to CD 10, with CD 1 representing the menstruation onset date. Factorial validity (exploratory factor a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…To confirm a diagnosis of PMDD, symptoms must be tracked for a period of a minimum of two symptomatic cycles ( 1 ). The most commonly used clinical tool used to track premenstrual symptom severity is the Daily Record of Severity of Problems ( 61 ). However, this tool does not concurrently track symptom severity of manic and depressive symptoms.…”
Section: Symptom Tracking In Comorbid Bipolar Disorder and Premenstrual Dysphoric Disordermentioning
confidence: 99%
“…To confirm a diagnosis of PMDD, symptoms must be tracked for a period of a minimum of two symptomatic cycles ( 1 ). The most commonly used clinical tool used to track premenstrual symptom severity is the Daily Record of Severity of Problems ( 61 ). However, this tool does not concurrently track symptom severity of manic and depressive symptoms.…”
Section: Symptom Tracking In Comorbid Bipolar Disorder and Premenstrual Dysphoric Disordermentioning
confidence: 99%
“…Another potential limitation of the study was the use of pen and paper to collect DRSP records, which could have resulted in missing or incomplete data. Exploring the use of smartphone apps to collect DRSP data could be beneficial to address this limitation [ 74 ]. This approach could reduce the rate of missing data and increase the percentage of completers.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported the additional information, which are marked in red in the attached Word file (Additional file 1 ).…”
mentioning
confidence: 99%